2019
DOI: 10.1142/s0192415x19500289
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin: A Natural Flavonoid Enhances the Survival of HUVECs against Oxidative Stress by Modulating AMPK/PKC Pathway

Abstract: Oxidative stress has been implicated in the pathogenesis of atherosclerotic cardiovascular diseases. Dietary supplementation of anti-oxidants has been reported to have beneficial effects on the prevention of atherogenic diseases. Luteolin (a natural flavonoid) has been shown to possess antimutagenic, antitumorigenic, anti-oxidant and anti-inflammatory properties. However, the effects and underlying molecular mechanisms of luteolin on cardiovascular systems are poorly explored. Therefore, the aim of the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…They note that daily supplementation with 100 mg/kg and 200 mg/kg luteolin reduced high blood pressure and oxidative stress, including lipid peroxidation (expressed as MDA) and protein carbonylation, among 40 male Wistar albino rats. Another study by Ou et al [82] found luteolin to have antioxidant potential against various parameters of oxidative stress, to protect against oxidative stress induced by hydrogen peroxide, a hydrogen radical donor, and reduce the production of ROS in human umbilical vein endothelial cells (HUVECs). The authors propose that luteolin may exert its effects through the regulation of protein kinase C. Luteolin has also been found to display inhibitory effects on the proliferation and migration of vascular smooth muscle cells, suggesting that it may also be a potential candidate for preventing and treating atherosclerosis [83].…”
Section: Honey Phenolics and Cardiovascular Diseasesmentioning
confidence: 99%
“…They note that daily supplementation with 100 mg/kg and 200 mg/kg luteolin reduced high blood pressure and oxidative stress, including lipid peroxidation (expressed as MDA) and protein carbonylation, among 40 male Wistar albino rats. Another study by Ou et al [82] found luteolin to have antioxidant potential against various parameters of oxidative stress, to protect against oxidative stress induced by hydrogen peroxide, a hydrogen radical donor, and reduce the production of ROS in human umbilical vein endothelial cells (HUVECs). The authors propose that luteolin may exert its effects through the regulation of protein kinase C. Luteolin has also been found to display inhibitory effects on the proliferation and migration of vascular smooth muscle cells, suggesting that it may also be a potential candidate for preventing and treating atherosclerosis [83].…”
Section: Honey Phenolics and Cardiovascular Diseasesmentioning
confidence: 99%
“…Reports of using honey and its related bee products (propolis, beeswax, pollen) in traditional medicine stretch back centuries, since the first reports from Sumer, and then in ancient Egypt, Greece, Rome, and Asia [5], due to their appreciated and renowned health benefits. However, despite the many hypotheses on the mechanisms for the numerous beneficial effects, honey's full potential has started to be unlocked only recently, with more comprehensive characterisations of its physicochemical composition (as described in Section 2 of this paper), and the further investigation of the medical activity of natural bioactive compounds also found in honey [6][7][8][9][10][11][12][13][14][15]. Honey has been shown to possess beneficial properties with diverse applications in otorhinolaryngology [16,17], respiratory tract diseases [18,19], cardiovascular diseases [20][21][22], metabolic disorders [23][24][25][26], oncology [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin is present in foods such as carrot, cabbage, tea, and apple and is found in Ugni molinae Turcz. [ 73 , 74 ]. Data show that luteolin (50 μ g/mL) increases the levels of GSH, the expression of GSH synthetase, and the activity of SOD and CAT in human colon cancer cells (HT-29) [ 75 ].…”
Section: Occurrence and Antioxidant Properties Of Anticoronavirus mentioning
confidence: 99%